Pengaruh Komitmen dan Motivasi terhadap Lingkungan Kerja Serta Dampaknya terhadap Kinerja Pegawai Kantor Camat Maro Sebo Ulu Kabupaten Batanghari - Budimansyah Budimansyah; M. Zahari; Sudirman Sudirman (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study was to describe the commitment, motivation, work environment and performance of the sub-district office of Maro Sebo Ulu, Batanghari Regency. Then to analyze the influence of commitment, motivation, work environment and performance of the sub-district office of Maro Sebo Ulu, Batanghari Regency, then analyze the influence of the work environment on teacher performance, then analyze the effect of commitment and motivation through the work environment on performance. This research is a research using descriptive and verification research methods, namely a method in examining a group of people, an object, situation and condition of a system of thought with the aim of making a description, a systematic picture according to the facts being investigated. The verification research aims to test the hypothesis about the influence of the variables in this study. This research involved 57 employees and from the entire population were taken as respondents in this study totaling 56 employees in the Maro Sebo Ulu sub-district except for the leadership or the head of the Service. Data were analyzed using SPSS.22. The results showed that commitment was in neutral conditions, motivation was in good condition, work environment was good and performance was also good, that commitment and motivation simultaneously and partially had a positive and significant effect on the work environment, commitment and motivation simultaneously and partially had a positive and significant effect on performance and work environment has a positive and significant effect on the performance of the sub-district office of Maro Sebo Ulu, Batanghari Regency.